Circadian oscillations of cytosolic free calcium regulate the Arabidopsis circadian clock - Ruiz, María Carmen Martí (Nat Plants, 2018)
In the last decade, the view of circadian oscillators has expanded from transcriptional feedback to incorporate post-transcriptional, post-translational, metabolic processes and ionic signalling. In plants and animals, there are circadian oscillations in the concentration of cytosolic-free Ca(2+) ([Ca(2+)](cyt)), though their purpose has not been fully characterised. We investigated whether circadian oscillations of [Ca(2+)](cyt) regulate the circadian oscillator of Arabidopsis thaliana. We report that in Arabidopsis, [Ca(2+)](cyt) circadian oscillations can regulate circadian clock function through the Ca(2+)-dependent action of CALMODULIN-LIKE24 (CML24). Genetic analyses demonstrate a linkage between CML24 and the circadian oscillator, through pathways involving the circadian oscillator gene TIMING OF CAB2 EXPRESSION1 (TOC1).